Effect of walnut flour (Juglans spp.) addition on wheat bread crumb porosity - Chochkov Rosen; Dimitrov Nikolay (BIO Web of Conferences)
Bread is one of the most consumed foods globally and incorporating walnut flour will enhance its nutritional value by including biologically active components. The porosity is a key characteristic of the sensory properties and overall acceptability of the bread crumb. The objective of this study was to investigate the effect of walnut flour on bread crumb porosity by employing image analysis. Six breads were prepared with mixtures of wheat:walnut flour in proportions from 100:0 to 85:15. The number of pores, pore size, total pore area, mean pore size and circularity of the bread crumbs were investigated. The number of pores and their density in 1 cm2 area decrease with an increase of the amount of walnut flour, while the total area of the pores and the average size of the pores increase. Circularity is low and the addition of nut flour has minor effect on it. The highest percentage of porosity is due to large pores. The area of large pores increases and the area of small pores decreases with the increase of walnut flour. The addition of walnut flour results in an uneven and rough structure of the bread crumb, compared with pure wheat flour bread.